Educational quality and regional disparity: one application of hierarchical model to Brazilian dataset - Sammara Soares; Tatiane Menezes (European Regional Science Association (ERSA), 2011)
The quality of the educational system is crucial to the most diverse socioeconomic and cultural aspects of a country. The objective of this paper is highlighting the importance of quality of education to explain the wide income disparities between Brazilian people. In face of such evidence, and considering the need to better understand the factors associated with education quality and efficiency, this study aims to investigate which factors are the most significant to determine elementary school students' performance in capital and small towns. For this purpose, it will be used the Brazilian Educational Search (SAEB) for 4th grades of elementary education. The estimation method is the hierarchical regression, which, in this work, will be structured into 2 levels, respectively: students, and school. The results suggest, after socioeconomic control, the positive correlation of principal's characteristic; class-time, kindergarten and presence of library to a better performance. In opposite way, the influence of professor's turnover seems to be quite harmful to determine the student's score in capital city and small towns respectively. These results can serve as aid to public policies aimed at equity and educational qualification.
Keywords: 330